Connective tissue injury in calf muscle tears and return to play: MRI correlation. Issue 14 (26th October 2017) - Prakash, Ashutosh; Entwisle, Tom; Schneider, Michal; Brukner, Peter; Connell, David
Abstract : Objective: The aim of our study was to assess a group of patients with calf muscle tears and evaluate the integrity of the connective tissue boundaries and interfaces. Further, we propose a novel MRI grading system based on integrity of the connective tissue and assess any correlation between the grading score and time to return to play. We have also reviewed the anatomy of the calf muscles. Materials and methods: We retrospectively evaluated 100 consecutive patients with clinical suspicion and MRI confirmation of calf muscle injury. We evaluated each calf muscle tear with MRI for the particular muscle injured, location of injury within the muscle and integrity of the connective tissue structure at the interface. The muscle tears were graded 0–3 depending on the degree of muscle and connective tissue injury. The time to return to play for each patient and each injury was found from the injury records and respective sports doctors. Results: In 100 patients, 114 injuries were detected. Connective tissue involvement was observed in 63 out of 100 patients and failure (grade 3 injury) in 18. Mean time to return to play with grade 0 injuries was 8 days, grade 1 tears was 17 days, grade 2 tears was 25 days and grade 3 tears was 48 days (p<0.001). Conclusion: The integrity of the connective tissue can be used to estimate and guide the time to return to play in calf muscle tears.